Fostering Early Interest in Electrical Engineering Through the Electro Goes to School (EGOTS) 2025 Initiative - Anggi Anugrah; Arsenio Ghifari; Zenisya Annelia Alimin; Andre Suwardana Adiwidya; Subekti Ari Santoso (Civiliza Publishing, 2026)
In the era of rapid technological advancement, a comprehensive understanding of fundamental electronic concepts has become indispensable for students to address future scientific and industrial challenges. In response to this need, the Electrical Engineering Student Association of Universitas Pembangunan Nasional “Veteran” Jakarta (HMTE UPNVJ) organized a community outreach program entitled Electro Goes to School (EGOTS) 2025. The event, conducted on September 26, 2025, was attended by 70 students from grades 11 and 12 of SMAN 82 Jakarta. The program comprised a semi–talk show presentation introducing the fundamentals of Electrical Engineering, including the department’s three concentrations, core academic courses, and professional career pathways. Furthermore, a project demonstration session was conducted in collaboration with three Student Study Groups (KSM), which are Ecovoltech KSM, Internet of Things (IoT) KSM, and Mechatronics KSM. The overall survey results of the EGOTS event showed positive feedback with a score of very good by 35 (54%) participants, good by 26 (40%) participants, quite good by 3 (5%) participants, and not good by 1 (1%) participant. This activity successfully enhanced participants’ understanding of electrical engineering principles and inspired greater motivation to pursue advanced studies in the discipline.